Using Transition Action Details (TAD) Strategy to Improve Writing Skills of Grade Ten Students of SMA Negeri 7 Palu - Aziza, Nuraziza Syaputri; Erniwati, Erniwati; Jamiluddin, Jamiluddin; Budi, Budi (Universitas Cokroaminoto Palopo, 2024)
The objective of this research is to find out if using Transition Action Details strategy can improve writing skills of grade ten students of SMA Negeri 7 Palu. The researcher used quasi experimental design consisting of 34 students in experimental class and 34 students in control class. Also, the researcher used purposive sampling. In collecting the data, the researcher gave pretest and posttest to both experimental class and control class. The data is calculated by using statistically analysis to find out the significant difference in students’ achievement before and after treatment. The researcher used 0.05 level of significance and 66 degree of freedom (df). The researcher found that the value of t-counted is 4.63 which is higher than the t-table of 1.669. It means that the hypothesis is accepted. In conclusion, using Transition Action Details strategy can improve writing skills of the sampled students.